PENGARUH DISIPLIN KERJA DAN KINERJA PENDIDIK TERHADAP GAYA KEPEMIMPINAN DI SMP NEGERI 12 LUBUKLINGGAU - Nisusmiati, Murlina; Fitria, Fitria; Mulyono, Hardi; Nasruddin, Nasruddin; Kurniawan, Ade (STKIP Persada Khatulistiwa Sintang, 2024)
The first problem is weak supervision and monitoring of the implementation of employee duties. Second, there is still a distribution of duties from the principal to employees which is not in accordance with the employee's expertise. This indicates that the leadership carried out has not been effective. Another problem with this research is that some teachers still do not adhere to time regulations, there are still teachers who do not make lesson plans. Based on this, this research was conducted to determine work discipline and teacher performance regarding leadership styles. The design of this research is quantitative research. This research uses observation, questionnaire, and documentation data collection methods. The analysis techniques used are simple linear regression analysis, correlation coefficient, t test, multiple linear regression analysis, coefficient of determination and F test. This research is expected to contribute to understanding how an effective leadership style can improve work discipline and teacher performance as well as provide recommendations to improve the quality of education in schools. The results of the research show that Work Discipline and Teacher Performance have a significant effect on the leadership style of the principal at SMP Negeri 12 Lubuklinggau.